On an Elliptic Equation of $p(x)$-Kirchhoff Type with Convection Term and Singular Weights - Zaki, Ayoub; Haddaoui, Mustapha; Bochiha, Walid (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we will use new compact embedding and by Galerkin's approach we prove the existence of at least one solution to a p(x)-Kirchhoff problem with convection term and singular weights.